Strömgren metallicities for intermediate-age and old star clusters - Piatti, Andres Eduardo (2020)
We report results that show that the straightforward star cluster metallicities obtained from Strömgren vby photometry are age-dependent and need to be corrected for further use. This outcome arises from the comparison of [Fe/H] values derived from Strömgren photometry with those metallicities published in the literature for 26 Large and Small Magellanic Cloud star clusters, whose ages range from ∼1 Gyr up to the oldest-known globular cluster ages in these galaxies. While deriving mean star cluster metallicities, we carried out a thorough selection of red giant branch candidates to comply with the Strömgren metallicity calibration validity regime. We paid attention to the effect of contamination by field stars, particularly those that lie inside the star clusters' radii, that are distributed along the star cluster red giant branches and that have [Fe/H] values covering a similar range as that for the selected stars. We find that the measured Strömgren metallicities are systematically more metal-poor than the published ones and that a quadratically age-varying function reproduces the relative metallicity values with an overall uncertainty of ∼0.05 dex. We finally performed a similar comparison relying on a fully independent approach, which consisted in using theoretical red giant branches of old globular clusters spanning [Fe/H] values from -2.0 up to 0.0 dex as standards. We then superimposed onto them the red giant branches of star clusters with ages in the range 1.0-12.5 Gyr and estimated their associated metallicities by interpolation. The derived theoretical relative metallicities follow a similar trend as a function of the star clusters' ages as what has been found from observations of star clusters.